2013
DOI: 10.1055/s-0033-1349843
|View full text |Cite
|
Sign up to set email alerts
|

Injuries among Talented Young Dancers: Findings from the UK Centres for Advanced Training

Abstract: The aim of the present study was to characterize the injuries of young dancers attending Centres for Advanced Training. 806 dancers, ages 10-18 years responded to surveys regarding their biological profile, dance experience and injury history, and were examined for their anthropometric profile. Of the 806 dancers, 347 reported an injury. Based on 4 age groups, the total hours of practice per week increased significantly with increasing age. Incidence of injuries per 1000 h of dance practice for dancers ages 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 15 publications
3
52
1
1
Order By: Relevance
“…Of those that did, 22 investigated female and male participants, 14 focused solely on females, and 1 included males only. The combined total of females reported was 2360 (range 928–58829) and males was 822 (range 230 31–28129). …”
Section: Resultsmentioning
confidence: 99%
“…Of those that did, 22 investigated female and male participants, 14 focused solely on females, and 1 included males only. The combined total of females reported was 2360 (range 928–58829) and males was 822 (range 230 31–28129). …”
Section: Resultsmentioning
confidence: 99%
“…Também, a entorse do tornozelo é frequente em bailarinos quando, após salto, chegam ao solo com o tornozelo em flexão plantar (32) . Em bailarinas, jovens ou experientes, verifica-se uma elevada taxa lesional, principalmente no joelho, tornozelo e pé, que está significativamente relacionada, entre outros fatores, com o número de horas de treino por semana em treinos coreográficos ou de estilo criativo (46) . Uma das preocupações de bailarinos/as é melhorar a sua potência muscular para executar saltos mais amplos e elevados que são fatores determinantes de performance.…”
Section: Razões Da Existência Do Controlo Ponderal Na Dançaunclassified
“…The risk of injury is one of the most common healthhazards in ballet. In general, the lower extremities appear to be the most common injured locations, followed by soft tissue disorders within the lumbosacral region [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, identifying any factor associated to injury occurrence in ballet is highly important. While studies repeatedly reported the association between intensity and frequency of training and practice with injury occurrence [8,9], there is a lack of studies that have examined the specific association between the body-built and injury prevalence in ballet dancers. This is especially important for 2 reasons.…”
Section: Introductionmentioning
confidence: 99%